Investigating Diabetes-associated Autoantibodies and Their Relationship to Clinical Characteristics in Children Diagnosed With Type 1 Diabetes - Niloofaralsadat Motamedi; Daniel Zamanfar; Fatemeh Rostamian Motlagh; Jamshid Yazdani Charati (Mazandaran University of Medical Sciences, 2024)
Background: Type 1 diabetes mellitus (T1DM) is an autoimmune disorder characterized by the destruction of insulin-producing beta cells in the pancreas, leading to insulin deficiency.  Objectives: This study determines the frequency of T1DM-specific auto-antibodies, namely glutamic acid decarboxylase, islet cell cytoplasmic, insulinoma-associated-2/tyrosine phosphatase, and insulin autoantibody.  Methods: This prospective cross-sectional study was conducted from March 2019 to December 2020. Registered T1DM patients under 18 years of age who visited the Diabetes Clinic of Bu Ali Sina Hospital in Sari City, Iran, were included. The autoantibody, clinical, and biochemistries profile of each participant was recorded. Results: A total of 190 children diagnosed with T1DM were included in the study. The mean age of the patients was 13.14±0.36 years. Based on the mono test, the highest prevalence was seen in islet cell cytoplasmic (104 [66.67%]). Also, based on multiple tests, islet cell cytoplasmic+glutamic acid decarboxylase had the highest prevalence (135 [49.63%]). Patients with positive insulinoma-associated-2/tyrosine phosphatase and islet cell cytoplasmic compared to negative insulinoma-associated-2/tyrosine phosphatase and islet cell cytoplasmic had higher age at diabetes onset (8.93±4.11 vs 7.73±4.33, P=0.02; 8.8±4.22 vs 6.81±4.1, P=0.01), receptively. The HbA1c level at T1DM onset in patients with positive insulin autoantibody was lower than negative insulin autoantibody (7.84±1.82 vs 9.41±2.35, P=0.0009). There was a significant difference in hyperglycemia with positive and negative insulinoma-associated-2/tyrosine phosphatase, in which the chance of positive insulinoma-associated-2/tyrosine phosphatase was 54% lower in hyperglycemia than in euglycemia (odd ratio=0.46 [0.22-0.96], confidence interval=95%, P=0.04). Conclusions: The islet cell cytoplasmic and islet cell cytoplasmic + glutamic acid decarboxylase had the most prevalence in T1DM patients in Northern Iran.